Analisis penggunaan QRIS terhadap peningkatan pendapatan UMKM - Alifia, Nadhifa; Permana, Erwin; Harnovinsah, Harnovinsah (Jurnal Riset Pendidikan Ekonomi, 2024)
Along with the rapid growth of digital media, various forms of digital transactions are also developing. One digital transaction tool that has grown significantly is the Quick Response Code Indonesian Standard (QRIS). The increase in the number of QRIS merchants and QRIS users correlates with the increase in the volume and nominal transactions processed by each merchant every year, including MSMEs. This research aims to conduct an analysis of the use of QRIS to increase MSME income. The research method was carried out using a descriptive qualitative approach. Research data comes from search results from various trusted sources, including official websites, academic literature, theses and national scientific journals that are relevant to the research topic. After thorough analysis and discussion regarding the impact of QRIS on increasing MSME income, it can be concluded that the growth in the number of QRIS users as well as the volume and nominal transactions per merchant is directly proportional to the increase in MSME income. This trend does not only occur in the Greater Jakarta area and Java Island, but occurs nationally throughout Indonesia. The increase in income from QRIS cannot be separated from the convenience offered to MSMEs who no longer need to make large investments in creating QR codes for various payment platforms. With QRIS, they can accept payments from various banks and digital payment providers. Apart from that, the increase in revenue was also due to QRIS' ability to serve customers of all age groups, because the younger generation tends to prefer digital payment methods over cash transactions.